Harmonic injection effects in backed-off helix travelling-wave tubes. A study by Eulerian analysis - Datta S.K.; Jain P.K.; Basu B.N. (My University, 2025)
The problem of second harmonic generation in a helix travelling-wave tube was studied by Eulerian hydrodynamical analysis. The correct regime of applicability of the Eulerian analysis, with respect to the rf input power drive and the interaction length of the device, was found a priori by validating the analysis against the more accurate Lagrangian analysis. Within this regime of applicability, which necessarily corresponds to the backed-off operation of the device, was studied the second harmonic generated in the device, with particular reference to its control by harmonic injection. In particular, the optimum values of the relative amplitude and phase of the additional second harmonic input signal relative to the main input signal were predicted for the minimum second harmonic output of the device.